Coconut Oil and Palm Oil Supplementation, as Agents of Methane Reducing in Goat Feed on Meat Quality - Erwin Hubert Barton Sondakh; Jerry Audie Donny Kalele; Friets Semuel Ratulangi (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
This research was conducted to examine feed containing coconut oil and palm oil on the quality of goat meat. Used as many as 20 goats aged + 1 year. Feed was given with a formulation of 60:40% forage and concentrates with a composition according based on needs of goats. This experiment used a CRD with 5 treatments and four replications. The treatments were R0: basal feed; R1 was basal feed added 0.5 mL of coconut oil; R2 was basal feed added 1 mL of coconut oil, R3 was basal feed added 0.5 mL of palm oil and R4 was basal feed added 1 mL of palm oil.  The Animals rearing was carried out for 60 days and followed by slaughter of cattle to measure the quality of the meat. The variables measured were pH, WHC, cooking loss, water content, crude protein, crude fat. The data obtained were analyzed by ANOVA. The results shof the meat gave no significant difference (P>0.05). Conclusion that supplementation of coconut oil and palm oil at the level until 1 mL can be used in goat feed.